2013
DOI: 10.1200/jco.2012.48.5805
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Open-Label, Phase III Study Comparing Irinotecan With Paclitaxel in Patients With Advanced Gastric Cancer Without Severe Peritoneal Metastasis After Failure of Prior Combination Chemotherapy Using Fluoropyrimidine Plus Platinum: WJOG 4007 Trial

Abstract: No statistically significant difference was observed between paclitaxel and irinotecan for OS. Both are reasonable second-line treatment options for advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
316
5
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 465 publications
(363 citation statements)
references
References 21 publications
25
316
5
17
Order By: Relevance
“…PTX arm was longer in the Japanese population (11.5 months) than in the Western population (5.9 months) in our study. This is in accordance with previous studies in the first-line and second-line setting reporting better survival outcome in Asian/Japanese patients than in Western patients [3,4,7,18,19]. In the present study, there were differences between the Japanese and Western patients in some important baseline characteristics (such as ECOG PS, TTP with first-line therapy, and number of metastatic sites) indicating that the Japanese patients may have been healthier (with less tumor burden) at the start of the trial.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…PTX arm was longer in the Japanese population (11.5 months) than in the Western population (5.9 months) in our study. This is in accordance with previous studies in the first-line and second-line setting reporting better survival outcome in Asian/Japanese patients than in Western patients [3,4,7,18,19]. In the present study, there were differences between the Japanese and Western patients in some important baseline characteristics (such as ECOG PS, TTP with first-line therapy, and number of metastatic sites) indicating that the Japanese patients may have been healthier (with less tumor burden) at the start of the trial.…”
Section: Discussionsupporting
confidence: 82%
“…Neutropenia was one of the most frequently reported adverse events in both treatment arms, and the incidence in the PL ? PTX arm was within the range of that reported in other Japanese and Western trials with a similar paclitaxel dose and schedule [7,[11][12][13]. Neutropenia was commoner in the Japanese population, but this could be managed safely, as indicated by the longer median duration of therapy in the RAM ?…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A previous phase III study comparing irinotecan with paclitaxel in patients with AGC whose diseases progressed after first line chemotherapy reported median PFS as 3.6 months, an equivalent result to Bang' s study (23). The response rate presenting in the phase II trial was also consistent to the results on PFS.…”
supporting
confidence: 76%
“…Compared with the best supportive care, first-line chemotherapy for advanced gastric cancer (AGC) improves survival time and quality of life (2)(3)(4); however, the median overall survival (OS) time is short (9-13 months) (5)(6)(7). Several previous studies have demonstrated that second-line chemotherapy confers a significant survival benefit over best supportive care in AGC, with median OS time ranging from 4 to 9.5 months (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%